2018
DOI: 10.1186/s12882-018-0894-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing dialysis withdrawal: a scoping review

Abstract: BackgroundResearch on factors associated with dialysis withdrawal is scarce. This study examined the predictors that might influence rate of dialysis withdrawal. Existing literature is summarized, analyzed and synthesized to identify gaps in the literature with regard to the factors associated with dialysis withdrawal.MethodsThis scoping review used a systematic search to synthesize research findings related to dialysis withdrawal and identified gaps in the literature. The search strategy was developed and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 48 publications
1
31
1
6
Order By: Relevance
“…Despite the higher prevalence of dialysis withdrawal and its significant association with death in ESRD patients, the phenomenon of dialysis withdrawal remains unclear [17]. There is a gap in the literature with regards to factors associated with dialysis withdrawal, mainly because of the scarcity of available literature and inconsistent findings across various studies [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the higher prevalence of dialysis withdrawal and its significant association with death in ESRD patients, the phenomenon of dialysis withdrawal remains unclear [17]. There is a gap in the literature with regards to factors associated with dialysis withdrawal, mainly because of the scarcity of available literature and inconsistent findings across various studies [17].…”
Section: Discussionmentioning
confidence: 99%
“…These contradictory and inconsistent findings might be account for in several ways. Authors have defined dialysis withdrawal as withdrawal due to different reasons and causes, such as discontinuation, withholding, treatment refusal by patients and caregivers, and technique failure [10][11][12][13][14][15][16][17]. Some studies have used small sample sizes, resulting in type II error (false negative) [10,11], and some have not addressed mental health factors, such as depression/anxiety, dementia, and bipolar disorder [18] related to dialysis withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…There are more than 120,000 and 700,000 people with CKD5 in the UK and USA, respectively. 2 Over the past 60 years, the dialysis population has transitioned from a relatively healthy 'single-disease' population of patients to a population with many chronic diseases and, therefore, a high burden of associated symptoms. Dialysis has transitioned from a bridge to transplant to destination therapy for many patients who will not be eligible for transplant.…”
Section: Epidemiological Considerationsmentioning
confidence: 99%
“…it decreases as the quality of life improved [4]. The rate of withdrawal of dialysis is higher among women compared to men, and older patients compare to younger [5]. Male gender is negatively associated with withdrawal of heamodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…Male gender is negatively associated with withdrawal of heamodialysis. There is no relation between withdrawal of hemodialysis and income, level of education, employment, and marital status [5]. A study carried out among patients on heamodialysis in Saudi, revealed that the mean age of the respondents is 51.7 years (± 15.4).…”
Section: Introductionmentioning
confidence: 99%